Carbon dioxide emissions and nitrogen and phosphorus mineralization patterns from soil amended with shoot and root residues of different wheat genotypes - Mbava, Nozibusiso; Zengeni, Rebecca; Muchaonyerwa, Pardon (Frontiers in Agronomy, 2025)
Crop residue incorporation into soil is one strategy for improving soil quality. While several studies have investigated the decomposition of different crop species, little is known about mineralization patterns amongst genotypes of the same crop. This study assessed the mineralization patterns of shoot (ST) and root (RT) residues from five wheat genotypes (LM70, LM75, BW140, BW152, and BW162), which were obtained from a drought-stress field trial. The ST/RT residue was mixed with 100 g of soil in airtight PVC containers and incubated for 120 days. Carbon dioxide (CO2) released during decomposition was trapped, whereas soil from each pot was analyzed for NH4+, NO3−, and extractable P throughout the incubation. The initial biochemical composition varied amongst genotypes and plant parts, with shoots exhibiting lower C:N and lignin content, and higher N and P concentrations, whereas the opposite was observed for roots. The STs also emitted higher net CO2 and mineralized higher net mineral N and P compared with RTs. LM70RT emitted the lowest CO2 (2.49 mg g−1 C), whereas BW140ST (11.3 mg g−1 C) and BW162ST (11.0 mg g−1 C) had the highest emissions. Net N mineralization initially increased before stabilizing by end of incubation, with BW152RT releasing the lowest (4.91 mg g−1 N), whereas BW162ST and BW140ST had the highest amounts (22.3 and 21.8 mg g−1, respectively). BW140RT also mineralized the lowest extractable P (0.98 mg g−1 P), whereas BW152ST had the highest (4.39 mg g−1 P). These results suggest that residue decomposition and nutrient release were influenced by the initial biochemical composition of wheat residues, which reflected the effects of drought stress during plant growth.